Assessment of Renewable Energy Deployment Roadmaps - Ignacio Mauleón (Energies, 2019)
This research implements a methodology to the joint assessment of the photovoltaic and onshore wind investment roadmaps put forward by the main institutions in the field, International Renewable Energy Association (Irena) and the International Energy Agency, to achieve a low carbon emissions economy with near zero net greenhouse gases emissions. The two energies taken together account for over 80% of the renewable energy deployments envisaged by both roadmaps. The assessment is conducted according to economic criteria (the levelized cost of energy, capital requirements and financial risks), and environmental (carbon avoided, its value, and its cost). Given the recent Intergovernmental Panel on Climate Change (IPCC) report on the urgency to tackle climate change, accelerated deployments of the roadmaps are assessed as well. Overall, it is found that the roadmaps are financially sound, even under an accelerated scenario. Possible limits to the deployment of renewable energies roadmaps derived from the availability of raw materials and other constraints are also discussed, showing likely constraints for lithium batteries but not for photovoltaic and wind energies.